TINJAUAN KRIMINOLOGIS TERHADAP PENCURIAN DI RUMAH IBADAH DI WILAYAH HUKUM KEPOLISIAN SEKTOR TAMPAN KOTA PEKANBARU - INNIKE DERISA; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Theft is a criminal offense which is done by taking other people’s belongings, especially theft in the house of worship, where a place of worship is now a favorite place for the perpetrators of theft. Theft in the house of worship is a criminal offense which is done by taking the goods are not privately owned but belong to the congregation without the owner’s permission and perfomed in the place of worship. Theft in the house of worship often occur because of the opportunities for such theft action. Can we know the place of worship was sparsely furnished wit a complete security system. The purpose of this thesis that: first, to find out the causes of the crime of theft in the house of worship in Police Sector Tampan, the second to find the usual modus operandi by criminals of theft in the house of worshi in Police Sector Tampan, third to know the constraints of Police sector Tampan ini preventing and combating acts of theft in the house of worship in Police sector Tampan.Type of research is a sociological juridical law it is the effort to approach problems examined with real legal nature or in accordance with the realities of life in the community. Sources of data used in sociological research is primary data and secondary data, secondary data is divided into primary legal materials, secondary legal materials and legal materials tertiary. Techniques used in data collection are interviews, questionnaire and literature study. While the analysis used is a qualitative manner, with the deductive method of reasoning.From the research, there are three main probelms that can be inferred. First, factors contributing to the crime of theft in the house of worship is economic factors, environmental factors and safety factor. Second, the modus operandi of the perpetrators of theft committed in the house worship, pretending to pretend to break, swap the bag and do the same when her ablutions. Third, obstacle in preventing and combanting the crime of theft in the house of worship due to the lack of witnesses and evidence, the minimal number of Police Sector Tampan and the lack of budget funds.Kata Kunci: Kriminologi- Pencurian- Penyelidikan